Polder Tidings - Yadav, Sudhir; Mondal, Manoranjan K.; Batas, Mary Ann; Jagadish, S.V. Krishna; Mandal, M. A. Sattar; Ali, Mohammad; Sarker, Mou Rani; Singaraju, Niyati; Parvin, Rokhsana; Sarker, Shilpi Rani; Bhattacharya, Jayanta (2023)
This issue of Polder Tidings presents a comprehensive overview of the key accomplishments and lessons learned from the “Pathways of scaling agricultural innovations for sustainable intensification in the polders of coastal Bangladesh (SIIL-Polder: Phase II)” project. The publication highlights the project's achievements in leveraging the unique agro-ecological conditions of the polders to enhance agricultural productivity. The issue discusses the agroecological potential of coastal Bangladesh, emphasizing the need for innovative water management and irrigation technologies to enhance crop yields and agricultural productivity. It reflects on the lessons learned from seven years of adaptive research, noting the importance of integrating qualitative research to understand farmers' perspectives and the socio-economic dynamics influencing agricultural practices. Key articles delve into the impact of climate change on coastal agriculture, the role of technology in agricultural development, and the strategic importance of mega-infrastructure projects in driving economic growth in these regions. The magazine also features insights from stakeholders, the potential for youth engagement in agriculture, the significance of gender empowerment, and the experiences of SIIL scholars.